2022
DOI: 10.1186/s13068-022-02201-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Yarrowia lipolytica for the sustainable production of β-farnesene from waste oil feedstock

Abstract: Background β-Farnesene is a sesquiterpene with versatile industrial applications. The production of β-farnesene from waste lipid feedstock is an attractive method for sustainable production and recycling waste oil. Yarrowia lipolytica is an unconventional oleaginous yeast, which can use lipid feedstock and has great potential to synthesize acetyl-CoA-derived chemicals. Results In this study, we engineered Y. lipolytica to produce β-farnesene from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…We hypothesized GPD1, CIT2, and MLS knockouts would increase malonyl-CoA accumulation by increasing acetyl-CoA availability, whereas DGA1 and DGA2 are targeted to divert the malonyl-CoA flux toward naringenin production from lipids. We observed that the knockouts of DGA1 and DGA2 did not increase naringenin production, contradicting the previous work on β-farnesene production . We hypothesize that it is because the knockouts were performed on a strain engineered to possess a high acetyl-CoA flux.…”
Section: Resultscontrasting
confidence: 93%
See 3 more Smart Citations
“…We hypothesized GPD1, CIT2, and MLS knockouts would increase malonyl-CoA accumulation by increasing acetyl-CoA availability, whereas DGA1 and DGA2 are targeted to divert the malonyl-CoA flux toward naringenin production from lipids. We observed that the knockouts of DGA1 and DGA2 did not increase naringenin production, contradicting the previous work on β-farnesene production . We hypothesize that it is because the knockouts were performed on a strain engineered to possess a high acetyl-CoA flux.…”
Section: Resultscontrasting
confidence: 93%
“…Several knockouts in both the tyrosine and malonyl-CoA pathways were designed based on inference from the literature. Double knockouts of DGA1 and DGA2 increased β-farnesene production by 56% as the lipid content was reduced to 8.72% from 26% . The addition of fatty acid inhibitor cerulenin increased naringenin production by 31.2% in engineered strains, pointing to the significance of fatty acid downregulation to increase malonyl-CoA-based molecules.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In recent years, oleaginous microbial hosts, especially the nonconventional yeast Yarrowia lipolytica , have been successfully developed for the production of various terpenoid molecules such as farnesene, amorphadiene, squalene, lycopene, and β-carotene. When compared to conventional model microbial hosts, such as E. coli and S. cerevisiae , Y. lipolytica was characterized by great advantages, including a strong pool of precursor acetyl-ConA, natural storage environment for hydrophobic compounds, numerous lipid droplets, and sufficient cofactor . In addition, Y. lipolytica is also generally recognized as safe (GRAS) by the American Food and Drug Administration (FDA) …”
Section: Biosynthesis Of C13-apocarotenoids In Microbial Hostsmentioning
confidence: 99%